Gastroblastoma with a novel EWSR1‐CTBP1 fusion presenting in adolescence. Issue 9 (7th June 2021) - Koo, Selene C.; LaHaye, Stephanie; Kovari, Bence P.; Schieffer, Kathleen M.; Ranalli, Mark A.; Aldrink, Jennifer H.; Michalsky, Marc P.; Colace, Susan; Miller, Katherine E.; Bedrosian, Tracy A.; Leraas, Kristen M.; Voytovich, Kyle; et al.
Abstract: Gastroblastomas are rare tumors with a biphasic epithelioid/spindle cell morphology that typically present in early adulthood and have recurrent MALAT1‐GLI1 fusions. We describe an adolescent patient with Wiskott‐Aldrich syndrome who presented with a large submucosal gastric tumor with biphasic morphology. Despite histologic features consistent with gastroblastoma, a MALAT1‐GLI1 fusion was not found in this patient's tumor; instead, comprehensive molecular profiling identified a novel EWSR1‐CTBP1 fusion and no other significant genetic alterations. The tumor also overexpressed NOTCH and FGFR by RNA profiling. The novel fusion and expression profile suggest a role for epithelial‐mesenchymal transition in this tumor, with potential implications for the pathogenesis of biphasic gastric tumors such as gastroblastoma.